RETRACTED : Evaluasi Penerapan Cobit 5 Pada Layanan Pengadaan Secara Elektronik (LPSE) - Hulukati, Stephan Adriansyah; Hikmawati, Nina Kurnia (P3M Politeknik Negeri Banjarmasin, 2018)
This article has been Retracted because the author has published in another journal at the same time.